Genetic characterization of an X-STR decaplex system in the State of Mato Grosso, Brazil: distribution, forensic efficiency and population structure - Martins, Joyce A.; Martins, Denise P.; Oliveira-Brancati, Camila I. F.; Martinez, Juliana [UNESP]; Cicarelli, Regina M. B. [UNESP]; Souza, Dorotéia R. S. (Springer Nature, 2017)
Studies with X-STR loci show population genetic substructure, which makes necessary the characterization of such markers in the different geographical and/or ethnic populations. Therefore, this study assessed the distribution and forensic efficiency of an X-STR decaplex system in the population of the State of Mato Grosso, as well as analysed the population structure of this State based on the aforementioned system. All X-STR markers were in Hardy–Weinberg equilibrium and linkage equilibrium, and the DXS6809 was the most informative marker. The power of discrimination value in females and males was 0.99999999995 and 0.9999994, respectively. Analysis of molecular variance indicated 1.10% (p < 0.00001) of heterogeneity among Europeans, Africans, Brazilians and other Latin Americans, and in relation to such groups, the population of the State of Mato Grosso showed lower genetic variation when compared with the Brazilian group (−0.10%, p = 0.67327). The genetic distance analysis showed lower values of FST (0.0004 ≤ FST ≤ 0.00331), with non-significant p value (p > 0.00024), between the populations of Mato Grosso and Mato Grosso do Sul, Paraná and the Southeast region of Brazil (except for one sample of Rio de Janeiro). FST values with significant p values (p ≤ 0.00024) were obtained between the population of Mato Grosso and Iberian, African and some Latin American populations. The X-STR decaplex system proved to be extremely useful in the population of the State of Mato Grosso, and the data obtained does not show the need for a specific forensic database for this State in relation to the Brazilian populations compared in this study, except for population of Rio de Janeiro.
Keywords: Brazil; Mato Grosso; Population structure; X-STR